2014
DOI: 10.4236/ojml.2014.44039
|View full text |Cite
|
Sign up to set email alerts
|

Phonemic Awareness and Reading Comprehension among Japanese Adult Learners of English

Abstract: Phonemic awareness (PA) accounts for individual differences in early reading achievement in English as a first language (L1), but its effect generally fades with age. However, in English as a second language (L2), PA may still explain variation in reading ability among the adult population, depending on the readers' L1 background. We examined the role of PA in the reading comprehension of L1-Japanese readers to closely examine the relationship between PA and reading comprehension. A path analysis revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…It may be that the process is similar to that reported by Yoshikawa & Yamashita (2014) for L1 reading among Japanese adults. It is also indicated here that this relationship may additionally be influenced by the learner"s first language being one that uses a non-alphabetic writing system, particularly noticeable in the case of the Japanese subjects, whose own written language employs an unusually deep orthography and has a different basic sentence structure to English.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…It may be that the process is similar to that reported by Yoshikawa & Yamashita (2014) for L1 reading among Japanese adults. It is also indicated here that this relationship may additionally be influenced by the learner"s first language being one that uses a non-alphabetic writing system, particularly noticeable in the case of the Japanese subjects, whose own written language employs an unusually deep orthography and has a different basic sentence structure to English.…”
Section: Resultssupporting
confidence: 62%
“…It also seems pertinent here to mention that, when Yoshikawa and Yamashita (2014) examined the role of phonemic awareness in the reading comprehension of L1-Japanese readers, their findings revealed that phonemic awareness made an indirect contribution to reading comprehension through decoding, which along with vocabulary knowledge directly supports reading comprehension. They also found evidence to support a role for phonemic awareness in their subjects" reading in English as a second language.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that the language skills proper of a native speaker in his L1 are the same mechanisms used for the further learning of an L2, then the reflection of Engen & Høien on PA, will be valid also for the acquisition of a foreign language. Yoshikawa & Yamashita (2014), instead, observed the presence of an indirect relationship between PA and RC, starting from a study on Japanese adults learning English as a FL. The study, based on a population of 71 Japanese native speakers students, aged between 18 and 24 years, compared the results obtained by these informants on four tested areas: PA, vocabulary, ISSN 1948-5425 2017 decoding of words and pseudo-words and RC.…”
Section: Theories On Phonological Awareness Development and Its Didacmentioning
confidence: 99%
“…In addition, phonological awareness was the only significant predictor of English reading at G5 for these EFL learners. However, phonological awareness only made an indirect contribution to reading comprehension in Japanese adult learners of English (Yoshikawa & Yamashita, 2014). In the study, both nonword reading and vocabulary significantly contributed to reading comprehension and jointly accounted for 18% of the variance, while phonological awareness significantly accounted for 7% of nonword reading.…”
Section: Reading and Phonological Awarenessmentioning
confidence: 99%